Are food-deceptive orchid species really functionally specialized for pollinators? - Fantinato, Edy; Del Vecchio, Silvia; Baltieri, Mattia; Fabris, Beatrice; Buffa, Gabriella (Ecological research, 2017)
Food-deceptive orchid species have traditionally been considered pollination specialized to bees or butterflies. However, it is unclear to which concept of specialization this assumption is related; if to that of phenotypic specialization or of functional specialization. The main aim of this work was to verify if pollinators of five widespread food-deceptive orchid species ( Anacamptis morio (L.) R.M. Bateman, Pridgeon & M.W. Chase, Anacamptis pyramidalis (L.) Rich., Himantoglossum adriaticum H. Baumann, Orchis purpurea Huds. and Orchis simia Lam.) predicted from the phenotypic point of view matched with the observed ones. We addressed the question by defining target orchids phenotypic specialization on the basis of their floral traits, and we compared the expected guilds of pollinators with the observed ones. Target orchid pollinators were collected by conducting a meta-analysis of the available literature and adding unpublished field observations, carried out in temperate dry grasslands in NE Italy. Pollinator species were subsequently grouped into guilds and differences in the guild spectra among orchid species grouped according to their phenotype were tested. In contradiction to expectations derived from the phenotypic point of view, food-deceptive orchid species were found to be highly functionally generalized for pollinators, and no differences in the pollinator guild spectra could be revealed among orchid groups. Our results may lead to reconsider food-deceptive orchid pollination ecology by revaluating the traditional equation orchid-pollination specialization.